2016
DOI: 10.1093/neuonc/now177
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training for neural recovery in a restricted sample of pediatric brain tumor survivors: a controlled clinical trial with crossover of training versus no training

Abstract: Background. Exercise promotes repair processes in the mouse brain and improves cognition in both mice and humans. It is not known whether these benefits translate to human brain injury, particularly the significant injury observed in children treated for brain tumors. Methods. We conducted a clinical trial with crossover of exercise training versus no training in a restricted sample of children treated with radiation for brain tumors. The primary outcome was change in brain structure using MRI measures of whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 47 publications
3
110
0
1
Order By: Relevance
“…Indeed, evidence suggests that physical exercise may restore neurogenesis in the irradiated rodent DG (Naylor et al, ). Moreover, a recent study found that physical activity increases hippocampal volume in PBTS treated with radiation and chemotherapy (Riggs et al, ). Future research should aim to characterize whether different types of interventions, such as exercise and cognitive training, promote widespread repair across the hippocampus or local repair in distinct subfields…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, evidence suggests that physical exercise may restore neurogenesis in the irradiated rodent DG (Naylor et al, ). Moreover, a recent study found that physical activity increases hippocampal volume in PBTS treated with radiation and chemotherapy (Riggs et al, ). Future research should aim to characterize whether different types of interventions, such as exercise and cognitive training, promote widespread repair across the hippocampus or local repair in distinct subfields…”
Section: Resultsmentioning
confidence: 99%
“…Riggs et al. found that aerobic exercise training increased white matter, hippocampal volume, and cognitive reaction times in children who were survivors of brain tumors, after a 12‐week training period, with increases still observed at 24 weeks . Additionally, in a noncancer population, Hillman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Controlled clinical trials provide compelling evidence of the role white matter plasticity plays in improved cognition in children and adolescents, as changes in white matter are observed following a direct intervention design that controls for maturation and learning. We recently demonstrated activity‐dependent white matter repair in children with a brain injury from their curative treatment for a brain tumor who participated in a physical exercise program (Riggs et al, ). Specifically, using a controlled crossover design, we showed that increased FA within the corpus callosum following a 12‐week exercise program predicted increased speed of processing in these children (Riggs et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated activity‐dependent white matter repair in children with a brain injury from their curative treatment for a brain tumor who participated in a physical exercise program (Riggs et al, ). Specifically, using a controlled crossover design, we showed that increased FA within the corpus callosum following a 12‐week exercise program predicted increased speed of processing in these children (Riggs et al, ).…”
Section: Introductionmentioning
confidence: 99%